Identification of Some New Tetrazole and Thiazolidine Derivatives Synthesized From 4-Chlorobenzoic Acid and Evaluation Their Antibacterial Effect - Maysoon Tariq Tawfiq (Journal of Global Pharma Technology, 2016)
The research  includes  the synthesis of some new derivatives of  tetrazole and thiazolidine  rings from the reactions of  2- (4-chlorophenyl)-5-hydrazinyl- 1,3,4-oxadiazole [4] with various substituted aromatic aldehydes  in absolute ethyl alcohol as  a  solvent and presence of glacial acetic acid as a catalyst to form Schiff's  bases [5-10]. The prepared new Schiff's bases [5 -10] reacted with sodium azide , and mercaptoacetic acid in THF to yield five membered rings  (tetrazole ring) [11-15], and (thiazolidine ring) [16-20]  in good products. The  spectral  methods  of  the   prepared  compounds  were  characterized  by FT.IR, and 1HNMR for compounds [9,13,14,and 19] , besides melting points were recorded , and the purity was checked through T.L.C. technique. Antibacterial activities for some of the synthesized compounds were examined.Keywords: Heterocyclic compounds, 4-Chlorobenzoic acid, Acid hydrazide, Oxadiazole, Schiff’s bases, Tetrazole, Thiazolidine, Biological activity.